Debittering and packaging studies on candied pomelo peels (Citrus Grandis Osbeck) - Ingles, Marita Y.
The main objective of he study was to debitter pomelo peels and to determine the packaging requirements of the candied product. Phase I involved the determination of the optimum boiling time and number of water changes. Four 1-kg batches were subjected to the following boiling times and water changes: 1) boiling time for 5 mins. in each 3 water changes; 2) boiling time from 10 mins. in each 3 water changes; 3) boiling time for 15 mins. in each 3 water changes; and 4)boiling water from 10 mins in each of 4 water changes. Two samples, boiled for 15 mins. in 3 water changes and boiled from 10 mins in each of 4 water changes were preferred by the panelists almost to the same degree. However, the minimum number of steps relative to the length of boiling and number of water changes had to be considered also so the sample boiled for 15 mins. in each 3 water changes was the procedure recommend. In Phase II, the sorption isotherm curve was determined by the Wink's Weight Equilibrium method. The critical moisture content was determined by subjecting 50-gm. lost of the samples packed in low density polyethylene bags at an accelerated relative humidity of 100% at 28°C-30°C. Weekly evaluation of the product showed that the critical moisture content was 44.9%. The computed maximum allowable water vapor transmission rate (WVTR) was computed to be 9.75 gm./m^2/day at 90% R.H. gradient at 28°C-30°C. The dimensional of the packaging material was 9 x 12.4 cm. with the length of storage at 180 days at 80% R.H. and 28°V. Packaging materials which meet this value are high density polyethylene and polypropylene unoriented.